28. EVALUATION OF GENERAL ANESTHESIA FOR CESAREAN SECTION IN PREGNANT WOMEN WITH PLACENTA ACCRETA (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate hemodynamic status during general anesthesia in caesarean section with placenta accreta and blood loss in surgery. Subjects and methods: A retrospective analysis of 42 cases of caesarean section with placenta accreta admitted from May 2015 to May 2025 at Hue Central Hospital.  Results: Among the studied patients, all had placenta previa and history of caesarean section was 100%. Ultrasonography accurately predicted placenta accreta in 92,86% of cases. All women underwent surgery under general anesthesia. Estimated blood loss ranged from 700 to 3500 ml, with an average of 1350 ml. The average red blood cell transfusion volume was 1050 ml (range 500-3050 ml), the average plasma transfusion volume was 3.2 units. Systolic and diastolic blood pressure dropped significantly 16 minutes after caesarean section when massive blood loss occurred. Bleeding disorder occurred 28.57%, of which 2 cases (4.78%) had disseminated intravascular complications. The rates of bladder and rectal invasion were 26.19% and 2.38%, respectively. Maternal and neonatal mortality was 0%.Conclusion: Anesthesia for the caesarean section with placenta accreta during the past ten years was quite safe for maternal and neonate, at Hue Central Hospital.
Keywords: Placenta accreta, cesarean section, blood loss in surgery.